2003
DOI: 10.1002/humu.10240
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screening of the N-myc downstream-regulated gene 1 (NDRG1) in patients with Charcot-Marie-Tooth Disease

Abstract: In a previous study, we have shown that N-myc downstream-regulated gene 1 (NDRG1), classified in databases as a tumor suppressor and heavy metal-response protein, is mutated in hereditary motor and sensory neuropathy Lom (HMSNL), a severe autosomal recessive form of Charcot-Marie-Tooth (CMT) disease. The private founder mutation R148X, causing HMSNL in patients of Romani ethnicity, has so far remained the only molecular defect linking NDRG1 to a specific disease phenotype. Here we report the first study aiming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 30 publications
(26 reference statements)
1
23
0
Order By: Relevance
“…An increase in granulin, a human glioma-associated growth factor gene (Liau et al, 2000), might indicate the possibility that tumor cells might try to escape from cell death by stimulating their growth. As responses to external stimulus, several genes including N-myc downstream regulated gene 1, which was classified in databases as a tumor suppressor (Hunter et al, 2003), and heavy metal-response protein were upregulated. Upregulation of microtubule-associated protein light chain 3B among cell growth and/or maintenance-related genes indicated activation of autophagic pathway (Kabeya et al, 2000).…”
Section: Involvement Of Caspase Activation and Mitochondrial Damage Imentioning
confidence: 99%
“…An increase in granulin, a human glioma-associated growth factor gene (Liau et al, 2000), might indicate the possibility that tumor cells might try to escape from cell death by stimulating their growth. As responses to external stimulus, several genes including N-myc downstream regulated gene 1, which was classified in databases as a tumor suppressor (Hunter et al, 2003), and heavy metal-response protein were upregulated. Upregulation of microtubule-associated protein light chain 3B among cell growth and/or maintenance-related genes indicated activation of autophagic pathway (Kabeya et al, 2000).…”
Section: Involvement Of Caspase Activation and Mitochondrial Damage Imentioning
confidence: 99%
“…The expression of NDRG1 in murine Schwann cells is enhanced during regeneration after sciatic nerve injury [11]. These findings are attributed to a stop codon non-sense mutation (R148X) [12] or to an exon-9-skipping mutation (IVS8-1G>A, S181-K198) [13] found in humans with hereditary motor and sensory neuropathy-Lom (HMSNL, also known as Charcot-Marie-Tooth type 4D disease). This disease is characterized by Schwann cell demyelination and concomitant early axonal impairment affecting both motor and sense peripheral nerves, and resulting in a loss of limb muscle function and touch sensation in adulthood [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The gene for Drg1 has been localized to the chromosome 8q24.3 (8). Mutations in the Drg1 gene are linked to hereditary motor sensory neuropathy (9, 10) and Drg1-deficient mice exhibited a progressive demyelination of peripheral nerves (11). Several in vitro studies indicated this gene to be the target of multiple regulatory pathways.…”
Section: Introductionmentioning
confidence: 99%